URGENSI PENELITIAN DALAM KEBERHASILAN DAKWAH - Hamlan Hamlan (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2017)
Research must be done for every activity that requires problems solving, similarly, to da'wah activities. One of the determinants of the success of da'wah is the mastery and recognition of da’I to the societies faced. Various aspects that need to be known by the da'i namely biological, geographical, economic, religious, education, profession and community. By research, it will facilitate the da'i to convey the messages of da'wah in accordance with the condition of society and the problems faced by them